Employee Engagement on Behavioral Performance: Study on public organization in Bandung, Indonesia - Iwan Sidharta (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
The demand for adapting new skills is an essential factor for employees to continue to be able to compete competitively. This research aims to determine employee commitment to Behavioral Performance. Researchers conducted a survey of government agency employees to test the influence of employee commitment on Behavioral Performance, conducting first-order and second-order tests. The research respondents were 87 employees at three government agencies in Bandung. The research results indicate that employees firmly commit to improving Behavioral Performance. The research implications suggest that government agencies should provide opportunities for employees to increase their commitment by adopting new skills, strengthening employee commitment through relevant direction strategies, providing constructive feedback, and emphasizing the consequences if duties and obligations are not fulfilled to provide optimal performance.